2021
DOI: 10.21560/spcd.vi.690079
|View full text |Cite
|
Sign up to set email alerts
|

Determining Teachers' Views on the Implementation Process of Home Schooling Services

Abstract: Bu araştırmanın amacı, öğretmenlerin evde eğitim hizmetlerini uygulama süreci ile ilgili görüşlerinin belirlenmesidir. Durum çalışması olarak desenlenen araştırmanın çalışma grubunu on altı öğretmen oluşturmak-tadır. Araştırmanın çalışma grubunun belirlenmesinde kolay ulaşılabilir durum örneklemesi yöntemi ben-imsenmiştir. Araştırmacılar tarafından geliştirilen yarı yapılandırılmış görüşme formu kullanılarak elde edilen veriler betimsel analiz tekniği kullanılarak analiz edilmiştir. Araştırmadan elde edilen bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
3
5
0
1
Order By: Relevance
“…Similarly, when the results obtained from the opinions of the special education teachers about the effects of homeschooling on their education were examined, it was found that they think that the home environment negatively affects their education in homeschooling, that the home environment where the education is given is an important variable and that the home environment has risks. These results of this research coincide with the results of Atbaşı and Pürsün (2021). Atbaşı and Pürsün (2021) also emphasized in their study that home environment is an important variable in homeschooling services.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, when the results obtained from the opinions of the special education teachers about the effects of homeschooling on their education were examined, it was found that they think that the home environment negatively affects their education in homeschooling, that the home environment where the education is given is an important variable and that the home environment has risks. These results of this research coincide with the results of Atbaşı and Pürsün (2021). Atbaşı and Pürsün (2021) also emphasized in their study that home environment is an important variable in homeschooling services.…”
Section: Discussionsupporting
confidence: 91%
“…These results of this research coincide with the results of Atbaşı and Pürsün (2021). Atbaşı and Pürsün (2021) also emphasized in their study that home environment is an important variable in homeschooling services.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Evde eğitim hizmeti bireyin evini okul ortamı olarak kullanılması temeline dayanmaktadır. Bu eğitim şekli süreğen hastalığı olan özel gereksinimli öğrenciler için eğitim fırsatlarının değerlendirilerek sonuçların iyileştirilmesi olarak değerlendirilebilir (Atbaşı ve Pürsün, 2021). Hastanede tedavi gören okul dönemi öğrencilerinin hastanede kaldıkları süreye bağlı olarak, eğitim ve öğretim yönünden akranlarına göre büyük kayıplar yaşadıkları ve bunun neden olduğu psikolojik etkiler çok sık karşılaşılan sorunlardan biri olarak karşımıza çıkmaktadır.…”
Section: Evde Ve Hastanede Eğitimunclassified